HGSHS-5:G—First results with the short version of the test for the Harvard Group Scale of Hypnotic Susceptibility and a comparison with the full version - Zech, Nina; Riegel, Bjoern; Rasch, Bjoern; Peter, Burkhard; Hansen, Ernil (Frontiers in Psychology, 2024)
Introduction: The HGSHS:A is one of the most commonly used measure of hypnotic suggestibility.However, this test suffers from low feasibility due to a time requirement exceeding one hour, and from a questionable representation of the normal population. Recently, a short version HGSHS-5:G was developed and published, and now first results are available. The scope of this investigation was to verify the assumption of equally positioned and normally distributed scores, resulting in equally sized suggestibility groups in a number of different studies with full or short versions of HGSHS, and to compare the results of the 11-item score with the 5-item score, the latter being calculated from either the full version or the short version test. Methods: Data of 21 studies with testing for HGSHS were analysed, 15 using the HGSHS:A full version and six using the HGSHS-5:G short version, including a total of 2529 data sets. Position and distribution of both 11-item score and the 5-item score were tested. Linear regression analysis was used comparing the two scores, as well as cross table and weighted Cohen`s kappa to determine the match of grouping into low and high suggestibility. To evaluate contributing factors to the observed differences in the study results a multifactorial analysis of variance was performed.Results: In the different studies position and distribution of scores, as well as group sizes for low and high suggestibles varied. All score distributions were found to be non-normal and shifted to the right from the middle score, the 11-item score more than the 5-item score. Correlation between both scores calculated from full version tests was moderate (R 2 = 0.69), as was the match of suggestibility grouping (κ = 0.58). Studies using the short version involving less students-dominated populations showed sufficient agreement with the full version, but lower scores caused by an increase in zero score. Conclusions: A normal population is not represented in most applications of HGSHS and grouping into low and high suggestibles varies, mainly due to different positions of score distributions. A direct comparison of full and short version of HGSHS tested in the same subjects is still missing.